Usability in a virtual learnig environement: a study at IFRN - Sales Júnior, Francisco Monteiro de (2016)
The research takes place in the context of studies on distance learning in Brazil, specifically in the model e-learning and from the use of virtual learning environments (VLE), considering the guidelines and progress of this educational form in Brazil. This work wants to contribute to the deepening of knowledge about the relationship between the areas of usability and pedagogy. The study presents an essentially qualitative approach, focusing both on the perception of the student and the teacher reflective context, where teachers investigate the practices. The object of research is the identification and adoption of the dimensions and the usability principles on pedagogical practices carried out in the Moodle, VLE used in the educational way considering distance learning of the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN) where the case study occurred. The study shows relevant by proposing to investigate how is the relationship between pedagogical practices and the adoption of usability, ensuring a reflection scenario to what extent the efforts and investments in distance learning at the institution have obtained success, notably the learning quality. The results and conclusions point to guiding elements for the correction and adjustment of teaching practices in pursuit of improvements in the educational way to the distance learning at the institution.